2019
DOI: 10.1017/s1049023x19004795
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative Endovascular Balloon Occlusion of the Aorta for Refractory Out-of-Hospital Non-Traumatic Cardiac Arrest – A Case Report

Abstract: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a percutaneous transfemoral balloon technique used in select centers for resuscitation and temporary hemostasis of bleeding patients. Several animal studies demonstrated that its application in non-traumatic cardiac arrest could enhance cerebral and coronary perfusion during cardiopulmonary resuscitation (CPR); despite this, there are few reports of its application in humans. This is a case report of REBOA application during a refractory out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…REBOA, by contrast, is lower cost and requires a skillset already mastered by emergency physicians. As demonstrated by Brede and Coniglio et al, REBOA may have a role in bridging patients to more advanced interventions such as ECMO, 19 an intra‐aortic balloon pump, 45 or cardiac catheterization.…”
Section: The Future Of Cardiac Arrestmentioning
confidence: 97%
See 1 more Smart Citation
“…REBOA, by contrast, is lower cost and requires a skillset already mastered by emergency physicians. As demonstrated by Brede and Coniglio et al, REBOA may have a role in bridging patients to more advanced interventions such as ECMO, 19 an intra‐aortic balloon pump, 45 or cardiac catheterization.…”
Section: The Future Of Cardiac Arrestmentioning
confidence: 97%
“…In June 2019, Coniglio et al reported on the first case where a REBOA catheter was used in the emergency department for NTCA as a bridge therapy to an intra‐aortic balloon pump 45 . Following aortic balloon inflation in the ED, the patient's ETCO 2 increased from 8–20 mmHg, hemodynamics stabilized, and sustained ROSC was achieved.…”
Section: Reboa In Human Non‐traumatic Cardiac Arrestmentioning
confidence: 99%
“…[10,11,18,21] Moreover, a few case reports have indicated that REBOA has an effect in humans with cardiac arrest. [22][23][24][25] Currently, there is only one report on the prospective clinical use of REBOA in the pre-hospital setting. [26] This study showed that pre-hospital REBOA procedure during resuscitation is feasible and did not negatively in uence the quality of ACLS.…”
Section: Study Rationalementioning
confidence: 99%
“…The studies also demonstrate increases in carotid artery blood flow [ 12 , 18 ], blood flow in the cerebral arteries [ 10 , 11 , 18 – 20 ], and cerebral perfusion pressure [ 10 , 11 , 18 , 21 ]. Moreover, a few case reports have indicated that REBOA has an effect in humans with cardiac arrest [ 22 25 ]. Currently, there is only one report on the prospective clinical use of REBOA in the pre-hospital setting [ 26 ].…”
Section: Introductionmentioning
confidence: 99%